Evaluation response of lettuce plant to foliar application with Potassium and Calcium under drought stress conditions (Damascus University Journal of agriculture sciences, 2024)
This research was conducted in  Erah Research Rtation/ Sewida Agricultural Research Center/ General Commission for Scientific Agricultural Research/ Syria in 2021. The aim of this research was studying the effect of foliar spraying with potassium (K) and calcium (Ca) on lettuce plants under drought conditions. The cultivation was achieved under three different levels of irrigation (100-80-60%), and foliar spraying was used with potassium (0-1-2 mg/l) and calcium (0-0.5-1mg/l). The results showed that gradual increase in the level of drought led to a gradual decrease in all indicators studied (morphological- physiological- productivity traits). In addition, the treatment with potassium and calcium improved all indicators studied compared to untreated plants under all studied drought levels. The results of the interaction between field capacity and spraying treatments also did not showed significant differences compared to the control in the irrigation level 100% for morphological and productivity indicators, while the treatments (2 g/ l K+1g/ l Ca ) were significantly superior  in nitrogen (3.781%) compared to the control (3.038%),  and (2 g/ l K+0.5g/ l Ca ) in phosphor element (0.5432%) compared to the control (0.4489%). As for the irrigation level 80%, (2 g/ l K+0.5g/ l Ca )  significantly  superior compared to the control in most of indicators studied, which recorded for the productivity indicator 12917 kg/ ha compared to the control 9583 kg/ ha, and the treatment (2 g/ l K+0.5g/ l Ca ) was continued to be superior  over the control in irrigation level 60%, registering for the productivity indicator 14410  kg/ ha compared to the control 8536 kg/ ha.
Keywords: Lettuce; Drought; Potassium; Calcium; Biological Yield